Fen Eğitimi Araştırmalarına Güncel Bakış - X - Ergün, Sude; Buz, Ceren; Yalçın Çelik, Ayşe; Kahraman, Aksel; Kutluca, Ali Yiğit; Yıldırım, Eda Nur; Güven, Gökhan; Girgin, Sönmez; Ata, Burçak; Kozcu Çakır, Nevin; Karlıdağ, Suna; Candan Helvacı, Sevcan; et al. (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-